Overproduction, Purification and Refolding of codon-optimized Hepatitis B Virus X Protein Subgenotype B3 in Escherichia coli BL21(DE3) - Anita Artarini; Armini Syamsidi; Anindyajati Anindyajati; Raymond R. Tjandrawinata; Debbie S. Retnoningrum (HAYATI Journal of Biosciences, 2022)
Hepatitis B virus (HBV) infects human and causes chronic liver infection, leading to liver cirrhosis and hepatocellular carcinoma. HBV X (Hbx) protein is known to interact with tumor suppressor protein p53 and block its translocation into the nucleus. This study outlines the overproduction of Hbx protein from HBV subgenotype B3 in Escherichia coli BL21(DE3), including its purification and refolding. The gene encoding Hbx was first codon-optimized and inserted into pET16b. The recombinant plasmid was then transformed into E. coli BL21(DE3) as an expression host. Optimization of Hbx expression was performed with variation of IPTG concentration and overproduction temperature. The results showed that Hbx protein was optimally induced by 0.075 mM IPTG and overproduction of Hbx at 17, 25, and 37°C exhibited no difference in protein level and location. The optimal refolding of Hbx was obtained using 0.1 M arginine prior to elution from Nickel column using 100 mM imidazole and 0.25 M arginine. Hbx migrates differently in SDS-PAGE reducing and non-reducing, while the melting curve pattern in TSA analysis changed after the refolding step. Essentially, this purified Hbx protein could potentially be used for interaction study with p53 and the inhibitor candidate of the protein.